OVERCOMING THE CHALLENGES OF DISTANCE LEARNING DURING THE COVID-19 PANDEMIC IN MACEDONIA: WHAT CAN WE LEARN FROM THE NEIGHBORING COUNTRIES? - Jancheski, Metodija; Jovanov, Mile; Jancheska, Sofija; Stankov, Emil (IATED, 2022)
The global health crisis caused by the COVID-19 pandemic required significant changes to the operations of educational institutions all across the world, as all classes were transitioned to remote instruction. Since these changes occurred abruptly, there was little time in creating strategies to effectively manage this transition. Unusual enrollment patterns and students’ grades during this period reflect these disruptions, not necessary the work of the individual students. It is important to also acknowledge that the educational systems in countries around the world were facing serious challenges even before the COVID-19 outbreak. These weaknesses became more evident during the pandemic which additionally contributed to weakening the quality of these educational systems. The existence of distance learning tools to some extent facilitated this abrupt transition from the traditional face-to-face teaching system to distance learning education during the pandemic, but not all countries in the world implemented the same exact set of distance learning tools and techniques within this short time span. In this paper, we aim to explore different tools and adaptation techniques for distance learning education implemented in developing countries with similar educational ecosystems. In particular, we are interested in distance learning frameworks adapted during the COVID-19 pandemic in four Balkan countries: Macedonia, Serbia, Bulgaria and Romania. We would like to examine the structure of online education in these countries, the extent to which they differ and whether they have yielded different results in students’ success and educators’ satisfaction levels. By conducting this case study, we also aim to identify the determinants of online effective learning. We would like to determine what online learning techniques have had a less positive effect on students’ learning effectiveness. Detecting the weaknesses of the system by looking at the challenges faced by students would enable to create practical solutions in order to improve their learning experience. Not only we are going to explore these issues from students’ point of view, but we are also including the educators’ perspective as an important variable in our study. We aim to analyze the difficulties educators in these four Balkan countries have been facing since the pandemic and how they have coped with them so far. Educators, just as students, come from a variety of technical backgrounds. While some have been exposed to the beauty and benefit of digital learning techniques and have previously used them in their teaching, others have not had the opportunity to explore them to the same extent. This is just one of the many variables we are taking into account when exploring the success of the transition from traditional to online teaching environment. We truly believe that developing countries can learn through the examples of their neighboring countries, especially since they have a tendency to have similar ecosystems, infrastructures and resources. By comparing the tools and techniques implemented in the online educational spheres in Macedonia, Serbia, Bulgaria and Romania, we aim to detect the issues during the transitional period of education in these countries and provide concrete suggestions to the existing frameworks. Our ultimate goal is to improve the overall experience of both students and educators in the educational system during this everlasting health crisis.
Keywords: covid-19 pandemic, distance teaching and learning